Assessing the Interplay between Economic Vulnerability and Health Resilience: A Multidimensional Analysis of Malaysia - Yew-Kang, Liew (Universiti Malaysia Sarawak, 2025)
Following periods of economic growth, nations often encounter various challenges, as evidenced by the diverse crises affecting Malaysia’s economy. In this context, addressing economic vulnerability and health resilience is crucial for ensuring that government policies are effectively aligned to enhance societal well-being. However, these concepts are inherently abstract and difficult to measure objectively. This study aims to address this gap by first constructing indexes for economic vulnerability and health resilience, grounded in the Economic Vulnerability Theory and the Social Determinants of Health framework. Subsequently, the study examines the interaction between these two dimensions. In addition to integrating data representing external economic conditions, the study successfully recruited 389 respondents from diverse socioeconomic backgrounds. Across three versions of the economic vulnerability and health resilience indexes, findings indicate that Malaysian society exhibits moderate levels of both economic vulnerability and health resilience. Moreover, results suggest that higher-income groups demonstrate greater economic vulnerability and health resilience. Additionally, indicators of economic vulnerability appear to influence the overall health resilience of Malaysian society. Ultimately, the computed indexes and their subsequent analysis provide a valuable benchmark for policymakers. By leveraging these findings, policymakers can refine existing strategies to better address societal needs, promote long-term sustainability, and enhance overall well-being.